(untitled) (Texas Journal of Multidisciplinary Studies, 2025)
This article presents a review of current scientific data on the use of PRP therapy in the management of premature ovarian insufficiency. The review addresses the main pathophysiological mechanisms of POI, clinical manifestations, and limitations of existing therapeutic approaches. Particular attention is given to the biological effects of PRP mediated by platelet-derived growth factors, including stimulation of angiogenesis, reduction of apoptosis, activation of dormant follicles, and improvement of ovarian reserve indicators. The results of preclinical and initial clinical studies are analyzed, along with potential limitations associated with the lack of standardized protocols for PRP application. The necessity for further randomized controlled trials and standardization of treatment protocols is emphasized to justify the clinical implementation of PRP in gynecological practice.